Integrated analysis of physiological responses and transcriptional regulation in kiwifruit under high temperature - Jiale Tang; Hai Xu; Ping Yuan; Kejia He; Mengjie Chen; Fanwen Bu; Rencai Wang; Feixiong Luo (BMC Plant Biology)
Abstract Background High temperature is one of the major natural problems resulting in delayed growth, development and decreased agricultural productivity. Kiwifruit is highly sensitive to high temperature at its entire development stage. In order to better understand the kiwifruit physiological and molecular mechanism, we conducted out a physiological parameters and transcriptome analysis under high temperature conditions using the leaf tissues of two species viz., thermosensitive Actinidia chinensis cv. Hongyang (Ac) and thermotolerant type Actinidia eriantha cv. Huate (Ae). Results The leaves from Ae plants were characterized as the underside leaf was covered by long and density intertwining trichome, thicker leaf tissues, low stomatal density when comparing with those from the Ac plants. When exposure to high temperature, the Ae plants maintained stabler photosynthesis and scavenged excess ROS by accumulating lower H2O2 capacity and increasing antioxidant capacity, significantly induced expression of antioxidant-related genes in comparison with the Ac plants. Moreover, global transcriptome profiling demonstrated that induced expression of genes related to endoplasmic reticulum (including heat shock protein), Ca2+ signaling pathway, glutathione metabolism, which might contribute to improved thermotolerance in Ae plants. Conclusion Above findings suggest that the significantly enhanced thermotolerance of Ae plants might attribute to leaf morphologic variation, stabled photosynthetic and improved antioxidant capacities, significantly induced higher differentially expressed genes (DEGs), such as HSP genes. Taken together, our results provide a dependable and useful information on the heat response in kiwifruit plants.